Paraquat induced acute kidney injury and lung fibrosis: a case report from Bangladesh - Isha, IT; Alam, ZHMN; Shaha, BK; Bari, MS; Bari, MZJ; Chowdhury, FR (BioMed Central, 2018)
Background: Since Bangladesh government issued a ban on the use of highly toxic WHO Class I pesticides, annual consumption of herbicides like Paraquat have been sharply increasing in the markets. Paraquat poisoning is an emerging public health threat and its high mortality rate is responsible for a signifcant number of deaths. Diagnostic limitations and unavailable sample at presentation have resulted in under-reporting and lack of awareness among the treating physicians, making Paraquat poisoning one of the most neglected toxicological emergencies. Herein, we present a case of Paraquat induced multi-organ failure and emphasis on pitfalls in the management. Case presentation: An 18-years-old healthy male was admitted in Sylhet M.A.G Osmani Medical College Hospital with history of attempted suicide by Paraquat ingestion. On admission, he had high serum creatinine but otherwise asymptomatic. He was discharged on day 10 when his renal functions returned to normal. But On day 15, he started having respiratory symptoms—unresponsive to any of the local treatments he received, and by day 30, he developed overt lung fbrosis. We present sequential blood picture, radiographs and CT scans demonstrating Paraquat induced kidney and lung injury over the course of 30 days. Conclusion:Paraquat poisoning can lead to death and fatal long-term consequences. All cases of Paraquat poisoning, regardless of symptoms, must be hospitalized and observed for early detection of complications. Distribution of Paraquat should be restricted and/or banned as 38 other countries have done so, which we believe will greatly reduce poisoning related mortality.